Simulizi ya Fungashada ya Migomba (Narrative of BBTV) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
The invasion of banana bunchy top virus (BBTV), the causal agent of the lethal bunchy top disease of banana and plantain, is threatening the continent’s most important banana production region in East Africa. The virus spread, confirmed in the 2020s in Tanzania and Uganda, is spreading fast.